Phono-semantic units in the “Diwan” of Yunus Emre and their continuity in modern Turkic languages - Utebekov, Сенбек; Suyinjanova, Жанар (Turkic Studies Journal, 2025)
This article provides a linguistic analysis of the shared Turkic lexical elements found in the poetic collection Diwan by Yunus Emre (13th-14th century), a prominent figure in Sufi literature who had a significant impact on the cultural life of Anatolian Turks and played a key role in shaping the Turkish literary language. By analysing the written heritage from a period when the Kazakh and Turkish literary languages were not yet fully formed, the study identifies historical and linguistic continuity, as well as phonetic,morphological and semantic correspondences between modern Turkic languages through the language of Yunus Emre. The study examines more than fifty words from the 'Diwan' that are considered archaic, dialectal, or vernacular in modern Turkish literary language and have fallen out of use, yet remain actively used in the Kazakh language. It provides comprehensive analysis of the phonetic, morphological and semantic development of these words. Ancient and dialectal forms of Turkish words are compared with their modern Kazakh counterparts, demonstrating their connection to the lexical systems of the Old Turkic, Karakhanid, Khorezm, Kipchak, Karluk and Chagatai periods. Particular attention is given to sound correspondence laws, such as the alternation of t ~ d, ş ~ j, j ~ y, ü ~ e, u ~ ı, g ~ ø, and v ~ u. The presence of the Kipchak and Karluk features, alongside Oghuz elements, in the 'Diwan' suggests that the language of the work is not based on a single dialect, but represents a multi-layered linguistic system. As a medieval representative of Turkic literature, Yunus Emre's language integrates the spiritual content of Sufi poetry, with the shared linguistic heritage, cultural memory and historical continuity of Turkic peoples. These findings facilitate the study of the preservation and loss of the shared Turkic lexicon, the evolution of words in individual languages, and the formation of literary language norms. By comparing the language of literary works such as Yunus Emre's 'Diwan', the interconnections between modern Turkic languages can be determined on a systematic, scientific basis.